Optimized gene transduction in human lung organoids: A high-efficiency method for advanced research applications - Jasmin Khateeb; Jady Liang; Yuchong Li; Thenuka Thanabalasingam; Julie Khang; Mirjana Jerkic; Giovanna Pellecchia; Bhooma Thiruv; Ya-Wen Chen; Ori Rotstein; Arthur S. Slutsky; Haibo Zhang (Communications Biology)
Abstract Human induced pluripotent stem cell (iPSC)-derived lung organoids, engineered to carry targeted genes, offer a robust platform for investigating mechanistic insights in lung research. Although lentiviral vectors (LVVs) are highly effective for stable expression due to their integrative properties, achieving efficient transduction in human iPSC-derived lung organoids poses a significant technical challenge, likely due to the complex structure of these organoids. In this study, we optimized a method to enhance LVV transduction efficiency by physically disrupting the organoids to increase surface area, followed by spinoculation to apply shear force during cell dissociation. This approach, combined with the use of an optimized culture medium, significantly improved transduction efficiency. The success of this method was validated at both the gene and protein levels using single-cell RNA sequencing (scRNA-seq) and various cellular and molecular assays. Our optimized transduction protocol may provide a valuable tool for investigating specific cellular and molecular mechanisms in development and disease models using human iPSCs-derived lung organoids.